2014
DOI: 10.1111/1744-7917.12092
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic study of the red palm weevil Rhynchophorus ferrugineus embryogenesis

Abstract: The red palm weevil (RPW), Rhynchophorus ferrugineus (Coleoptera: Curculionidae), is an invasive, concealed and destructive tissue borer, and it becomes a lethal pest of the palm family of plants and has been reported to attack 20 palm species around the globe. Here we report a systematic transcriptomic study on embryogenesis of RPW, where we analyze the transcriptomes across five developmental stages of RPW embryogenesis, involving four embryonic stages (E1, E2, E3 and E4) and one larval stage (L1). Using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 96 publications
1
10
0
Order By: Relevance
“…Also, we identified the enrichment of Rho guanyl-nucleotide exchange factor activity (GO: 0005089), which is a modulator in the signaling pathway of Ras/MAPK and Wnt. Previous studies have shown that this activity is associated with neuronal growth cone and planar cell polarity formation [42, 43]. In B. mori , consistent with [30], we identified the enrichment of monooxygenase activity (GO: 0004497), which might be associated with detoxification.…”
Section: Resultssupporting
confidence: 84%
“…Also, we identified the enrichment of Rho guanyl-nucleotide exchange factor activity (GO: 0005089), which is a modulator in the signaling pathway of Ras/MAPK and Wnt. Previous studies have shown that this activity is associated with neuronal growth cone and planar cell polarity formation [42, 43]. In B. mori , consistent with [30], we identified the enrichment of monooxygenase activity (GO: 0004497), which might be associated with detoxification.…”
Section: Resultssupporting
confidence: 84%
“…MFC, STDEV, and interquartile of expression level are the most commonly-used metrics to evaluate the variation among the data, with CV as the most popular parameter to evaluate expression stability of genes (Benedito et al, 2008 ; Severin et al, 2010 ; Wang et al, 2010 ; Daines et al, 2011 ; Graveley et al, 2011 ; Yin et al, 2015 ). Typically, the top 1,000 expressed transcripts with the lowest CV values in contrasting environments are taken as the stably expressed genes (Zhu et al, 2008 ; Van Hiel et al, 2009 ; Severin et al, 2010 ; Yin et al, 2015 ), with cut-off threshold values that are typically CV < 16 or < 20% (Benedito et al, 2008 ; Severin et al, 2010 ; Wang et al, 2010 ). An alternative method for selection of stably expressed genes is to choose genes whose RNA-seq has a sufficiently low CV of its logarithmically transformed RPKM and logarithmically transformed transcript copy numbers (threshold typically CV < 4%) (Fernández-Aparicio et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Limiting mitochondrial data to a handful of genes illustrates this point well as resolution fades rapidly [ 8 ]. Larger data volumes are now available from nuclear genome sequencing, either in terms of entire genomes [ 88 90 ], or transcribed genomes [ 91 , 92 ]. Each of these approaches has their own disadvantages with respect to high cost and labor intensity.…”
Section: Discussionmentioning
confidence: 99%